Evaluating the performance in the environmental management and reverse logistics in companies of plastic sector: an integration of fuzzy AHP, DEMATEL and TOPSIS methods (2021)
The plastic industry is considered one of the most dynamic industries with the highest competitive projection in the country [1]. Thanks to the advances of this industry, new products have been developed with various applications at industrial, commercial, service levels, and society’s daily lives. Plastics are highly demanded their chemical and physical properties, versatility, and low cost. However, many challenges are arising from the growth in consumption and the dynamics of the plastics industry, such as the prices of raw materials, substitute products of plastic, the demands of consumers, government, and other interested parties with the impact of plastics on the environment during the different stages of their life cycle. Concerning the life cycle of the plastic products is especially determinant the post-consumption, where plastic waste presents a low percentage of recycling and a prolonged period of degradation, being a product questioned for its negative environmental implications. In this sense, companies in the sector must implement different strategies and tools to evaluate their environmental performance, considering the product life cycle. In the world, there are various government regulations for the responsible use of plastics. International methodologies focused on sustainable environmental management in the products, processes, and organizational level have also been developed, such as the product life cycle approach, reverse logistics, and the ISO 45001 standard. However, it is necessary to create objective and analytical methodologies for evaluating environmental management and reverse logistics that provide solutions for the plastic industry, helping companies comply with applicable legal requirements and standards, and supporting decision-making processes. Concerning the decision-making is a complex process given the complexity of the sector and the multiple criteria taken into account when evaluating and establishing improvement strategies. In the literature review, we found several studies with the application of a multicriteria combined approach focused on selecting plastic recycling methods, location of plastic processing centers, eco-design of plastic products, and selection of suppliers. Despite these considerations, the research-oriented on applying integrated methodologies for evaluating performance in the environmental management and reverse logistics in the plastic industry, under multiple criteria and uncertainty, are mostly limited and with the exciting potential of development. Therefore, this document presents a hybrid methodology for evaluating the performance in the environmental management and reverse logistics in the plastic industry by applying two techniques of Multi-criteria Decision Methods (MCDM) uses in environments under uncertainly. First, the fuzzy Analytic Hierarchy Process (FAHP) is applied to estimate the initial relative weights of criteria and sub-criteria. The fuzzy set theory is incorporated to represent the uncertainty in the judgments of decision-makers. Then, the Decision-making Trial and Evaluation Laboratory (DEMATEL) was used for evaluating the interdependences between criteria and sub-criteria. FAHP and DEMATEL are later combined for calculating the final criteria and sub-criteria weights under vagueness and interdependence. Subsequently, the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) was used to rank the companies of the plastic industry. Finally, we detect improvement opportunities for the companies of the plastic sector